2020
DOI: 10.1111/ger.12522
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a community health worker intervention to improve the oral health of older Chinese Americans: A pilot study

Abstract: Objective To evaluate the acceptability of a community health worker (CHW) intervention designed to improve the oral health of low‐income, urban Chinese immigrant adults. Background Given that both dental caries and periodontitis are behaviourally mediated, biofilm‐based diseases that are largely preventable with attention to regular oral hygiene practices and preventive dental visits, strategies to arrest or even heal carious lesions and high‐quality maintenance care and plaque control without the need to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Control group: usual care 1.5 mos Not clear Improved SWAL-QoL, increased tongue pressure & reduced oral dryness Lee et al, (2021) [ 103 ] Oral health education via smartphone app developed in this study & via PowerPoint lectures to non-app users. Control group: usual care 1.25 mo Not clear Improved oral health knowledge & perception & reduced dental plaque & tongue coating scores amongsmartphone users Northridge et al, (2021) [ 104 ] Training on proper toothbrushing & flossing techniques. Encouraged regular dental visits & brushing with fluoride toothpaste & addressed any expressed concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Control group: usual care 1.5 mos Not clear Improved SWAL-QoL, increased tongue pressure & reduced oral dryness Lee et al, (2021) [ 103 ] Oral health education via smartphone app developed in this study & via PowerPoint lectures to non-app users. Control group: usual care 1.25 mo Not clear Improved oral health knowledge & perception & reduced dental plaque & tongue coating scores amongsmartphone users Northridge et al, (2021) [ 104 ] Training on proper toothbrushing & flossing techniques. Encouraged regular dental visits & brushing with fluoride toothpaste & addressed any expressed concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Alguns artigos defendem que, devido ao estado de saúde de alguns idosos, é necessária a atenção à saúde bucal especializada, ou seja, aquela realizada por profissional odontogeriatra. (Karawekpanyawon, et al, 2022;Northridge et al, 2021;Tenani, et al, 2020;Schimazzaki et al, 2020;Iwasaki et al, 2018;Watanabe et al, 2018;Wright et al, 2017;Castrejón-Perez et al, 2017). Essa condição é ocasionada, geralmente, por doença e falta de acesso a serviços odontológicos.…”
Section: Discussionunclassified
“…(Choi et al, 2021;Lee et al, 2020). Pessoas idosas dependentes apresentam limitações e precisam de assistência de outros na realização de atividades diárias que causam debilidades crônicas e vão se apresentar como barreiras ao tratamento odontológico, levando também à não cooperação do idoso com o cuidado (Kenny et al, 2021;Northridge et al, 2021;Wong et al, 2020;Nomura et al, 2020;Wee et al, 2020;Seo et al, 2019). Dentre esses idosos, muitos ainda possuem dentes e suas necessidades requerem que o prestador de cuidados seja capacitado.…”
Section: Discussionunclassified
“…As such, capacity building the CHWs to provide oral health services could help overcome accessibility, affordability, and acceptability barriers to dental health services in impoverished and marginalised communities. This is further reinforced by a pilot study that demonstrated a higher acceptability for CHWs oral interventions amongst Chinese Americans 39 . Our findings also revealed a higher preference for and satisfaction with CHWs services owing to their proximity within communities and affordability in comparison to formal health services.…”
Section: Practice and Research Implicationsmentioning
confidence: 90%